Serum lipids mediate the association of per- and polyfluoroalkyl substances exposure and age-related macular degeneration - Xiaodong Chen; Jiaqi Li; Ningda Xu; Xuewei Li; Jiarui Li; Qianwen Guo; Jia Zhang; Heng Miao; Lvzhen Huang (PLoS ONE, 2025)
Background This study aims to investigate the connection between serum lipids, per- and polyfluoroalkyl substances (PFAS), and age-related macular degeneration (AMD) risk and assess whether serum lipids mediate the association between PFAS and AMD. Methods 1605 participants were enrolled from NHANES 2005–2008. Four serum PFAS levels with high detective rates, including perfluorononanoic acid (PFNA), perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), and perfluorohexane sulfonic acid (PFHxS) were examined. Restricted cubic spline analysis (RCS) and weighted quantile sum (WQS) analysis were employed to detect nonlinear and mixed exposure effects. Results PFOS level was associated with any AMD (OR, 1.54; 95% CI, 1.12 to 2.11; P = 0.011), early AMD (OR, 1.43; 95% CI, 1.06 to 1.95; P = 0.024), and late AMD (OR, 3.35; 95% CI, 1.55 to 7.23; P = 0.004) risk. PFHxS (OR, 1.72; 95% CI, 1.01 to 2.93; P = 0.045) and PFOA (OR, 2.10; 95% CI, 1.21 to 3.63; P = 0.011) levels were associated with late AMD risk. The RCS showed a nonlinear connection between PFOS exposure and AMD risk (P nonlinear = 0.006). WQS analysis indicated a positive relationship between mixed PFAS exposure and AMD risk (OR, 1.34; 95% CI, 1.03 to 1.75; P = 0.030). Serum total cholesterol (TC) and high-density lipoprotein (HDL) cholesterol were associated with AMD risk (ORTC, 1.005; 95% CI, 1.001 to 1.009; P = 0.026. ORHDL, 1.028; 95% CI, 1.014 to 1.042; P<0.001), and mediated the relationship of PFOS exposure and AMD risk, with mediation proportions of 5.73% (P = 0.020) and 7.27% (P = 0.032), respectively. Conclusions PFOS exposure was connected with AMD risk and serum TC and HDL mediated this relationship.